Indications for hand and glove disinfection in Advanced Cardiovascular Life Support: A manikin simulation study - Bushuven, Stefan; Bansbach, Joachim; Bentele, Michael; Bentele, Stefanie; Gerber, Bianka; Reinoso-Schiller, Nicolas; Scheithauer, Simone (Frontiers in Medicine, 2023)
Background and Aim: There are no investigations on infection control precautions (ICP) during cardiopulmonary resuscitation (CPR) despite these patients are at high risk for healthcare associated infections. We aimed at evaluation the number ICP per CPR-case in general and the fraction that could be accomplished without delay for other life-saving techniques by standardized observations. Materials and Methods: In 2022 we conducted four days of Advanced Cardiac Life Support (ACLS) courses with 4 to 5 providers practicing on 33 ACLS case vignettes with standard measurements of chest compression fractions and ICP indications. Nine health care workers (six nurses and three physicians) participated. Results: 33 training scenarios came up with 613 indications for hand disinfection. Of these 150 (24%) occurred before patient contact and 310 (51%) before aseptic activities . In 282/310 (91%) of these indications with the highest impact for patient safety the medication-manager was responsible, in 28/310 (9%) the airway-manager. Depending on the scenario, 56 to 100% (mean 84.1%, SD± 13.1%) of all indications could have been accomplished without delaying patient resuscitation. Conclusion: To our knowledge, this is the first study investigating the feasibility of ICP in a manikin CPR study. Even if due to study set up feasibility is overestimated, the fundamental conclusion is, that a relevant part of the WHO indications for hand disinfection can be implemented without compromising quality in acute care, thus increasing the overall quality of patient care.